The Issue of Dual-Morphemes in Arabic: A Morpho-Syntax Study - Mochammad Indra Yumanto; Mohammad Nurunnasry; Abdoul Jabalibizmungu (State Islamic University (UIN) of Sunan Ampel Surabaya, Indonesia, 2021)
This research aims to find out the different arguments and opinions about the Morpheme “Tatsniyah”. The research combined morphological and structural studies in their analysis of the placement of words in the sentence, and the method used by the researcher in this issue is the descriptive approach, where the researcher described the problematic facts of the Morpheme “Tatsniyah” in the Arabic language. The result of this study are The first, opinions of nahwu scholars on the morpheme “Alif” in “Tatsniyah” : (a) the morpheme “Alif” is the letter “I’rob”. (b) the morpheme “Alif” is “I’rob”. (c) the morpheme “Alif” is the proposition “I’rob”. (d) the morpheme “Alif” is “Mabni”. (e) the morpheme